MIŁOSNE POZNANIE JAKO WIDZENIE, CZYLI OPHTHALMOI SYBARYTY I ASCETY - Rybowska, Joanna (Collectanea Philologica, 2013)
The article discusses the role of the eyes and sight in the process of perceiving the world and another person according to Greek spiritual culture. This regards two types of perception: one which results from the desire of its subject, as well as one which appears involuntarily causing sicknesses of the soul and body. The remedia amoris of ancient mystics and ascetics are analyzed, as well.